2022
DOI: 10.1242/dev.199995
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling enhances bone regeneration in the zebrafish mandible

Abstract: Loss or damage to the mandible due to trauma, treatment of oral malignancies, and other diseases is treated using bone grafting techniques that suffer from numerous shortcomings and contraindications. Zebrafish naturally heal large injuries to mandibular bone, offering an opportunity to understand how to boost intrinsic healing potential. Using a novel her6:mCherry Notch reporter, we show that canonical Notch signaling is induced during the initial stages of cartilage callus formation in both mesenchymal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…HEYL, HEY1, and HES1 are effectors of the Notch pathway in fibrosis promotion [ 17 , 18 ] and are up‐regulated upon Notch signaling ligands binding to NOTCH receptors. [ 19 , 20 ] Here, we studied the expression of these genes during meniscus development. HEYL was only expressed in smooth muscle cells and pericytes during embryonic stages (E24 and E35 weeks) and hardly expressed at other stages or in other cell populations ( Figure 7 A,B ), suggesting that HEYL may play pivotal role in the critical stage of meniscus fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…HEYL, HEY1, and HES1 are effectors of the Notch pathway in fibrosis promotion [ 17 , 18 ] and are up‐regulated upon Notch signaling ligands binding to NOTCH receptors. [ 19 , 20 ] Here, we studied the expression of these genes during meniscus development. HEYL was only expressed in smooth muscle cells and pericytes during embryonic stages (E24 and E35 weeks) and hardly expressed at other stages or in other cell populations ( Figure 7 A,B ), suggesting that HEYL may play pivotal role in the critical stage of meniscus fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, several of these putative novel genes, including Ptn, Tnc, Unc5c, and Fbln7, were also found to be expressed above threshold in mouse limb RNA-seq and scRNA-seq datasets (Ayturk et al, 2020;Duan et al, 2020;Sebastian et al, 2021). In addition, orthologs for most of these novel candidate genes are present in the genome of other vertebrates, including bony fishes, reptiles, amphibians, and cartilaginous fishes, and even some invertebrates, but only a few have been shown to be expressed in chondral bones of nonmammalian vertebrates, such as frog and fish (Nalbant et al, 2005;Geurtzen et al, 2014;Russell et al, 2014;Square et al, 2015;Barske et al, 2020;Kraus et al, 2022). Also, many of these novel putative core cartilage GRN genes have been found to be expressed in OA cartilage, and even to have a role during the progression of this skeletal disease, further supporting the importance of these genes during cartilage development (Mentlein 2007;Johnson et al, 2015;Sun et al, 2018;Zhang et al, 2018;Bhattaram and Jones 2019;Rice et al, 2019;Chakraborty et al, 2020;Hasegawa et al, 2020;Shi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of Notch signaling promotes the differentiation of MSCs into osteoblasts and bone mineralization and suppresses osteogenesis via inhibiting the Wnt/β-catenin pathway ( Luo et al, 2019 ). Recently, Kraus et al (2022) showed that Notch signaling activation could accelerate cartilage callus conversion into bone and increase bone repair, whereas the inhibition of the signaling pathway delays the transformation of the cartilage callus into bone. In another study, Goel et al (2019) reported that Notch signaling suppression in osteoclasts improves bone formation rate and healing in mice, characterized by larger bony calluses and increased bone mineral density.…”
Section: Importance Of Angiogenesis In Bone Development and Repairmentioning
confidence: 99%